2020
DOI: 10.1038/s41467-020-15326-5
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of cell surface markers and establishment of monolayer differentiation to retinal pigment epithelial cells

Abstract: In vitro differentiation of human pluripotent stem cells into functional retinal pigment epithelial (RPE) cells provides a potentially unlimited source for cell based reparative therapy of age-related macular degeneration. Although the inherent pigmentation of the RPE cells have been useful to grossly evaluate differentiation efficiency and allowed manual isolation of pigmented structures, accurate quantification and automated isolation has been challenging. To address this issue, here we perform a comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…We further acknowledge that the RPE cell models we employed may contain small subsets cells in a variably differentiated state that have a transcriptional landscape deviating from that of the fully differentiated population. To characterize this further experiments utilizing multiplex flow cytometry to directly link markers of RPE differentiation (e.g., Plaza Reyes et al, 2020) to synthetic promoter mediated reporter gene expression would be possible.…”
Section: Discussionmentioning
confidence: 99%
“…We further acknowledge that the RPE cell models we employed may contain small subsets cells in a variably differentiated state that have a transcriptional landscape deviating from that of the fully differentiated population. To characterize this further experiments utilizing multiplex flow cytometry to directly link markers of RPE differentiation (e.g., Plaza Reyes et al, 2020) to synthetic promoter mediated reporter gene expression would be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that our iPSC-RPE were insufficiently matured, which delayed the concomitant cellular events. In that regard, efforts for quantitative quality control to assess maturity instead of image-based analyses are emerging ( Plaza Reyes et al, 2020 ). Parallel studies with both genetic backgrounds are warranted in order to delineate the specific roles of each PRPF gene.…”
Section: Discussionmentioning
confidence: 99%
“…Erdogan et al reported that AT-MSCs in New Zealand rabbits did not express CD73 and CD90 [ 58 ], while Chen et al detected the expression of CD90 [ 59 ]. Some markers appeared already at the optic vesicle stage but did not remain highly expressed in the later differentiation stage [ 74 ].…”
Section: Mscs and Mscs-exosomes: Cell Selection And Preparationmentioning
confidence: 99%